Temperature measurement and analysis of postharvest agricultural products associated with thermal disinfestations - Rongjun, Yan; Zhi, Huang; Rui, Li; Hankun, Zhu; Bo, Ling; Wang, Shaojin (International Journal of Agricultural and Biological Engineering, 2013)
Hot air and hot water treatments are practical, environmentally-friendly and non-chemical heating methods, which are widely used for postharvest insect control and quality preservation in agricultural products. Taking apple and pear as representative fruits, this study mainly analyzed influences of their thermal properties, diameter, and medium speed on the heating rates of fruits through their real-time measured temperatures at surface and center. Based on the reported thermal death kinetic models of the target codling moth, the minimum heating time was estimated to achieve 100% insect mortality. The results showed that the heating rates in fruits decreased gradually with the increasing depth from the surface to the center. With increasing heating time, the heating rate became small. The apple was heated faster than the pear. Hot water was more effective than hot air in treating fruits. Increasing hot air speed increased the heating rate but increasing water circulating speed had no clear effects on the heating rate. Based on the measured temperature-time history of the fruit center, the minimum heating time could be effectively determined for codling moth control through the estimated total equivalent thermal lethal time. The results could provide reliable validation data for the computer simulation and a scientific basis to improve the hot air and hot water treatments.